L'examen médical périodique chez la personne âgée - Beaulieu, Marie-Dominique (1984)
The general approach to prevention in elderly patients differs from that for younger patients. In the elderly, most of the preventive activites performed by family physicians are tertiary. Prevention and cure of disease often overlap. The major health problem in elderly patients is the development of progressive incapacity. The evaluation of risk factors for this condition is the principal purpose of the periodic health examination of these patients. This article summarizes the principal recommendations for the periodic health examination of the elderly and discusses barriers to their implementation.